Proceedings of the 2018 8th International Conference on Education and Management (ICEM 2018) 2019
DOI: 10.2991/icem-18.2019.67
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Reform of Emplyment-oriented Curriculum in Higher Education

Abstract: With the rapid development of society and economy, higher education in China has shown a high momentum. The types, levels and specifications of running schools of various colleges and universities in China are very distinctive and unique, and their talent training modes are also more diversified. The employment-oriented cultivation of application-oriented talents not only meets the requirements of The Times, but also meets the needs of higher education personnel training mode. The implementation of the employm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…As such, the study indicated that some reforms in terms of teaching and learning, particularly employment-oriented teaching, can be applied through programmes and courses offered at HEIs. Such reforms not only can benefit individuals by deepening students' understanding of their future career, but also can balance the supply and demand of market needs (Sun, 2019). Besides that, improvements in professional curriculum also can benefit today's students.…”
Section: Teaching and Learning Development Programmementioning
confidence: 99%
“…As such, the study indicated that some reforms in terms of teaching and learning, particularly employment-oriented teaching, can be applied through programmes and courses offered at HEIs. Such reforms not only can benefit individuals by deepening students' understanding of their future career, but also can balance the supply and demand of market needs (Sun, 2019). Besides that, improvements in professional curriculum also can benefit today's students.…”
Section: Teaching and Learning Development Programmementioning
confidence: 99%
“…During the meshing process of a helical gear, one end of the gear teeth enters the mesh first and gradually transitions to the other end and finally exits the mesh. The contact line on the tooth surface changes from short to long and then to short, and the load on the gear teeth during alternating meshing is gradually added and then removed [1]. Due to the existence of this alternating load, the helical gear is prone to failure such as tooth breakage, tooth surface peeling, and excessive wear.…”
Section: Introductionmentioning
confidence: 99%
“…Pengembangan bakat yang berorientasi penerapan pekerjaan tidak hanya memenuhi persyaratan waktu, tetapi juga kebutuhan mode pelatihan tenaga kependidikan tinggi. Implementasi gagasan berorientasi kerja dalam pelatihan bakat pendidikan tinggi berarti pengamatan peran sosial masa depan dari pos-pos kejuruan dan mata pelajaran pendidikan dalam proses pengambilan keputusan dan implementasi pendidikan (Sun, 2019).…”
unclassified